Marine Transform Faults and Fracture Zones: A Joint Perspective Integrating Seismicity, Fluid Flow and Life - Hensen, Christian; Duarte, Joao C.; Vannucchi, Paola; Mazzini, Adriano; Lever, Mark A.; Terrinha, Pedro; Géli, Louis; Henry, Pierre; Villinger, Heinrich; Morgan, Jason; Schmidt, Mark; Gutscher, Marc-André; et al. (Frontiers in Earth Science, 2019)
Marine transform faults and associated fracture zones (MTFFZs) cover vast stretches of the ocean floor, where they play a key role in plate tectonics, accommodating the lateral movement of tectonic plates and allowing connections between ridges and trenches. Together with the continental counterparts of MTFFZs, these structures also pose a risk to human societies as they can generate high magnitude earthquakes and trigger tsunamis. Historical examples are the Sumatra-Wharton Basin Earthquake in 2012 (M8.6) and the Atlantic Gloria Fault Earthquake in 1941 (M8.4). Earthquakes at MTFFZs furthermore open and sustain pathways for fluid flow triggering reactions with the host rocks that may permanently change the rheological properties of the oceanic lithosphere. In fact, they may act as conduits mediating vertical fluid flow and leading to elemental exchanges between Earth’s mantle and overlying sediments. Chemicals transported upwards in MTFFZs include energy substrates, such as H2 and volatile hydrocarbons, which then sustain chemosythetic, microbial ecosystems at and below the seafloor. Moreover, up- or downwelling of fluids within the complex system of fractures and seismogenic faults along MTFFZs could modify earthquake cycles and/or serve as “detectors” for changes in the stress state during interseismic phases. Despite their likely global importance, the large areas where transform faults and fracture zones occur are still underexplored, as are the coupling mechanisms between seismic activity, fluid flow, and life. This manuscript provides an interdisciplinary review and synthesis of scientific progress at or related to MTFFZs and specifies approaches and strategies to deepen the understanding of processes that trigger, maintain, and control fluid flow at MTFFZs.